Preliminary studies of the tardigrada communities from a polymetallic nodule area of the deep South China Sea - Wang, Xiaogu; Bai, Lifen; Wang, Chunsheng; Lu, Bo; Li, Yujie; Lin, Qinyi; Huang, Xinyu; Fontoura, Paulo (Frontiers in Marine Science, 2023)
Abstract The knowledge about marine tardigrades from the South China Sea is very scarce with only four species from shallow waters recorded until now. The present study investigates the structure and diversity of tardigrade communities from the deep-sea (1517–1725 m bsl) at 8 stations in a manganese nodule area of the South China Sea. A total of 151 collected arthrotardigrades belong to 11 genera (Angursa, Batillipes, Coronarctus, Euclavarctus, Exoclavarctus, Halechiniscus, Moebjergarctus, Raiarctus, Rhomboarctus, Tanarctus and Tholoarctus), representing 17 species. Six species are new to Science (five Angursa species and one Halechiniscus species). Two Angursa species (Angursa sp. 4 and Angursa sp. 3) were the most abundant (25.2% and 14.6% repectively), followed by Moebjergarctus sp. (13.9%). The total number of species recorded in the South China Sea is near the global estimate (estimators of Bootstrap and Jacknife1 predict 19 and 21 species respectively). Specimens were mostly (90.7%) distributed in the upper layer of the sandy-mud sediment (0–1 cm). SIMPROF test shows the composition of tardigrade communities in all stations was no significantly different. In different stations the number of species, the Shannon-Wiener diversity index and the Pielou’s evenness index ranged from 4 to 10; 1.94 to 2.87, and 0.75 to 1.00 respectively. Since the deep sea is increasing threatened by some principal anthropogenic impacts (waste deposition, oil and gas extraction, deep-sea mining and fishing), we hope that the results obtained in this study can provide some basic information on the diversity and structure of tardigrade communities that, in the near future, can contribute to assist people to manage human activities and to protect the vulnerable deep-sea areas.